The impact of initiating quality of care improvement protocols on intensive care unit length of stay in patients undergoing coronary artery bypass grafting: An insight from a nascent program. (2nd May 2022) - Manla, Y; Bhatnagar, G; Gobolos, L; Aljabery, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Prolonged intensive care unit (ICU) length of stay (LOS) post coronary artery bypass grafting (CABG) constitutes a major challenge for both patients and cardiac surgery teams. While Identifying predictors of prolonged patients' stay in the ICU can further optimise ICU resource utilization, the role of initiating QOC improvement protocols aimed to reduce ICU LOS for these patients has been widely advocated. Therefore, we aim in our study to evaluate the overtime impact of initiating QOC improvement protocols on ICU LOS and present patient characteristics predicting prolonged ICU stay in patients undergoing CABG in a nascent program. Methods: We included consecutive patients (n=976) undergoing CABG at a newly established tertiary centre between June 2015 and September 2021. Data on baseline characteristics and presentation, in addition to intraoperative details and outcomes, were collected retrospectively. Patients with prolonged (≥48h) and short (<48h) ICU LOS were compared by appropriate testing methods. Predictors of prolonged ICU LOS were determined by multivariable logistic regression. Continuous development of ongoing protocols to improve QOC was taken, including but not limited to; enhancing diabetic control, coronary perfusion and renal function. Trends in prolonged ICU LOS were determined using Joinpoint Software of the National Cancer Institute to calculate the average annual percentage change (AAPC). Results: QOC improvement protocols initiation was associated with a 33.7% reduction in the proportion of patients having prolonged ICU LOS post- CABG between 2015 to 2021 ( AAPC: -5.3, 95%CI [-7.7, -2.9], p<0.001) . Overall, 56.4% (551/976) of patients had prolonged ICU LOS. In comparison to individuals with short ICU LOS, patients who overstayed in the ICU were significantly older, females, diabetic, with higher burden of peripheral vascular disease (Table). On presentation, the prolonged LOS group was featured by worse NYHA class, higher rates of acute myocardial infarction (MI), lower ejection fraction (EF), higher serum creatinine and more frequently required preoperative intra-aortic balloon pump (IABP) insertion (Table). Aortic cross-clamp time and type of surgery were comparable between groups. Unfavorable outcomes were noticed in the prolonged ICU LOS group regarding postoperative adverse events and mortality. On multivariable logistic regression, age, female gender, NYHA class ≥II, MI on presentation, preoperative creatinine level, preoperative EF and preoperative IABP placement were independent predictors for prolonged ICU LOS (Figure). Conclusion: In this study, initiation of QOC improvement protocols was associated with a significant reduction in prolonged ICU LOS. While multiple risk factors prolonging ICU LOS were identified, future studies are required to further incorporate these risk factors into ongoing protocols aimed to optimise resources utilisation and enhance the QOC in CABG patients.